Studying the Phenol Degradation in Synthetic Wastewater by Catalytic Wet Air Oxidation Process in Batch Reactor - Yaseen AL Kindi, Ghayda; Hammoodi AL Ani, Faris (International Journal of Engineering and Technology, 2018)
The current paper studies the viability of using a Batch reactor, by five types of Al-Fe pillared clay that prepared from five regions in Iraq for phenol degradation in synthetic wastewater. The operation condition study through variables in (pH, pressure, temperature, pillared load, phenol load). The findings have illustrated that phenol degradation could be increase via incrementing temperature, pressure, pillared load and degrease in phenol load. Phenol good degradation proportion which was 97 %, has been achieved at optimum proportion (pH= 3.9, temperature = 150 Â°C, pressure = 3.5 MPa, in addition to phenol concentration = 500 mg/l). The two models power-law and Langmuirâˆ’Hinshelwood have been usedÂ Â to study the catalytic kinetics of the phenol degradation. From results shown the activation energy for every response equivalent to (37114.014 j/mol) for Anbar (37795, 48783.9, 36628, 40785 j/mol) for Erbil, Mosul, Baghdad and Basra respectively. It was proved that the reaction in this study is under kinetics control.Â Â Â